Effects of a novel microbial fermentation medium produced by Tremella aurantialba SCT-F3 on cigar filler leaf - Zhang, Qianying; Yang, Shuanghong; Yang, Zhen; Zheng, Tianfei; Li, Pinhe; Zhou, Quanwei; Cai, Wen; Wang, Yue; Zhang, Juan; Ji, Xiaoying; Li, Dongliang (Frontiers in Microbiology, 2023)
Introduction: Adding a fermentation medium is an effective way to improve the quality of cigar tobacco leaves. Methods: A novel microbial fermentation medium produced by an edible medicinal fungus, Tremella aurantialba SCT-F3 (CGMCC No.23831) was used to improve the quality of cigar leaves (CFLs). Changes in sensory quality, chemical components, volatile flavor compounds (VFCs), and the structure and function of microbes were investigated during the fermentation process. Results: The sensory quality of CFLs supplemented with the T. aurantialba SCT-F3 fermentation medium significantly improved. Adding the fermentation medium increased the total alkaloid, reducing sugar, total sugar, and 12 VFCs significantly. A total of 31 microbial genera were significantly enriched, which increased the microbial community's richness and diversity. Microbial functions increased, including nucleotide biosynthesis, amino acid biosynthesis, fatty acid and lipid biosynthesis, nicotine degradation, and nicotinate degradation. During fermentation, the total alkaloid, reducing sugar, and total sugar content decreased. The richness and diversity of the microbial community decreased, whereas bacterial enzyme activity increased. At the end of fermentation, the sensory quality was excellent. The microbial structure gradually stabilized, and functional genes were low. The contents of the four Maillard reaction products and three nicotine degradation products increased significantly. 2-Ethyl-6-methylpyrazine, methylpyrazine, D,L-anatabine, β-nicotyrine, nicotinic degradation products, and total nitrogen were significantly and positively correlated with sensory quality. Methylpyrazine, D,L-anatabine, and β-nicotyrine were negatively correlated with Luteimonas, Mitochondria, Paracoccus, Stemphylium, and Stenotrophomonas. Conclusion: This research provides not only a new microbial fermentation medium that utilizes edible and medicinal fungi to improve the quality of fermented CFLs, but also new ideas for the development and application of other edible medicinal fungi to improve the quality of cigar tobacco leaves.